Influence of Instagram Clothing Advertisements on the Purchase Decision of Female Youths - Olumuji , Emmanuel Olukunle; Akinwalere , Ifedayo; Akinrinola, Daniel Gbolahan; Alayaki, Mofiyinfunoluwa (COMMENTATE: Journal of Communication Management, 2025)
The study explored the impact of Instagram clothing advertisements on the purchasing decisions of female youths aged 18–35 years in Nigeria. Guided by the Reception Theory, the study employed a survey research design, distributing structured questionnaires to 385 respondents selected via stratified random sampling. Data were analyzed to evaluate the frequency of Instagram use for clothing ads, the platform's appropriateness as an advertising medium, and strategies for effective clothing advertisements targeting female youths. The findings revealed that while Instagram is widely used for viewing and engaging with clothing advertisements, this interaction does not strongly translate into actual purchases. Most respondents cited product quality, price and brand reputation as key factors influencing their purchase decisions. Additionally, the study found that Instagram advertisements significantly enhance fashion trend awareness and inspire new styles among young women. However, their direct influence on purchase behavior is moderated by economic factors such as income and affordability. This study highlights the critical role of product characteristics and pricing strategies in shaping consumer choices within the social media landscape. The findings emphasize the need for advertisers to bridge the gap between high engagement rates and purchase conversions through targeted and incentive-driven advertising strategies.